STUDYING THE ELEMENTS OF THE TECHNOLOGY OF GROWING HIGH-QUALITY COTTON FROM THE NAMANGAN-77 VARIETY OF COTTON IN THE CONDITIONS OF THE MEADOW SAZ SOILS OF THE FERGANA REGION (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about the study of the elements of the technology of growing high-quality cotton from the Namangan-77 variety of cotton in the conditions of the grassland saz soils of the Fergana region of our country, and this process is considered.